Effects of age and eccentricity on visual target detection - Gruber, Nicole; Müri, René M.; Mosimann, Urs P.; Bieri, Rahel; Aeschimann, Andrea; Zito, Giuseppe A.; Urwyler, Prabitha; Nyffeler, Thomas; Nef, Tobias (Frontiers in Aging Neuroscience, 2014)
The aim of this study was to examine the effects of aging and target eccentricity on a visual search task comprising 30 images of everyday life projected into a hemisphere, realizing a ± 90° visual field. The task performed binocularly allowed participants to freely move their eyes to scan images for an appearing target or distractor stimulus (presented at 10°; 30°, and 50° eccentricity). The distractor stimulus required no response, while the target stimulus required acknowledgment by pressing the response button. 117 healthy subjects (mean age=49.63 years, SD=17.40 years, age range 20-78 years) were studied. The results show that target detection performance decreases with age as well as with increasing eccentricity, especially for older subjects. Reaction time also increases with age and eccentricity, but in contrast to target detection, there is no interaction between age and eccentricity. Eye movement analysis showed that younger subjects exhibited a passive search strategy while older subjects exhibited an active search strategy probably as a compensation for their reduced peripheral detection performance.